Pengaruh Kecepatan, Kelentukan Dan Kelincahan Terhadap Kemampuan Menggiring Bola Pemain Futsal Vamos Academy Padang - Rahmat Hidayat; Ridho Bahtra; Alnedral; Aldo Naza Putra; Randi Kurniawan (Jurnal Penelitian Pendidikan IPA, 2025)
Dribbling ability is one of the main skills that every futsal player must have to support performance on the field. This study was conducted to understand how speed, flexibility, and agility affect the dribbling ability of futsal players at Vamos Academy Padang. This study uses the path analysis method with purposive sampling technique. The instruments used include a 20 meter sprint speed test, agility test with zig-zag run test, flexibility test using sit and reach, and dribbling ability test through slalom dribbling test. The results showed that: (1) speed has a significant direct effect on dribbling ability with a significant value of 0.321; (2) flexibility also has a significant effect on dribbling ability with a significant value of 0.470; (3) agility significantly affects dribbling ability with a significant value of 0.240; (4) no significant effect of speed on dribbling ability through agility (0.164); (5) no significant effect of flexibility on dribbling ability through agility (0.077); and (6) speed, flexibility, and agility simultaneously have a significant effect on dribbling ability. In conclusion, speed, flexibility, and agility are important factors that directly affect the dribbling ability of futsal players.